The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Multispecies grasslands sustain on-farm forage productivity and quality while reducing nitrogen fertilizer inputs - Bobby Zetterlind; Pedro Janssen; Rob Geerts; Tim Visser; Anthonie Stip; Marie Jasmijn Zwetsloot; Ellis Hoffland; Nick van Eekeren (Plant and Soil, 2025)
Aims Species-rich grasslands are proposed to promote biodiversity and reduce nitrogen (N) fertilization while maintaining productivity. However, the effectiveness of this strategy remains uncertain, particularly since grasslands with varying species richness are managed differently. We compared biomass yield and forage quality of three grassland management types varying in species richness and N fertilization levels in an on-farm context. Methods We compared biomass yield and forage quality of three grassland management types: permanent grassland ( Lolium perenne L. dominated) and multispecies grassland (sown with grasses, forbs, and legumes) fertilized with 0, 150, and 300 kg N ha⁻ 1 , and unfertilized semi-natural grassland (highly species-diverse) at twelve farm locations over two years. Results Multispecies grasslands with 150 kg N ha⁻ 1 produced yields similar to permanent grasslands fertilized with 300 kg N ha⁻ 1 due to higher legume cover and biological N 2 fixation. Nitrogen fertilization negatively impacted legume cover and likely reduced biological N 2 fixation. Multispecies grassland differed less in in terms of yield over two years with varying weather conditions, suggesting enhanced drought tolerance. Semi-natural grasslands had the highest species richness but the lowest biomass yields and forage quality. Conclusions Transitioning from permanent- to multispecies grasslands presents a promising diversification strategy for livestock farmers aiming to improve sustainability and biodiversity, while reducing N fertilization and maintaining productivity. Yet, species richness remains substantially higher in semi-natural grasslands at the cost of reduced biomass yield and forage quality. Optimization of N fertilization should be considered to improve persistence of legumes and forbs in agricultural multispecies grasslands.

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Dynamic modulations of effective brain connectivity associated with postural instability during multi-joint compound movement on compliant surface - Tim Lehmann; Anton Visser; Tim Havers; Daniel Büchel; Jochen Baumeister (Experimental Brain Research, 2025)
Random fluctuations in somatosensory signals affect the ability of effectively coordinating multimodal information pertaining to the postural state during movement. Therefore, this study aimed to investigate the impact of a compliant surface on cortico-cortical causal information flow during multi-joint compound movements. Fifteen healthy adults (7 female / 8 male, 25.9 ± 4.0 years) performed 5 × 20 repetitions of bodyweight squats on firm and compliant surface. Motor behavior was quantified by center of pressure (CoP) displacements, hip movement and the root mean square of the rectus femoris activity. Using source space analysis, renormalized partial directed coherence (rPDC) computed subject-level multivariate effective brain connectivity of sensorimotor nodes. Bootstrap statistics revealed significantly decreased medio-lateral CoP displacement ( p < 0.001), significantly increased velocity of medio-lateral hip motion ( p < 0.001) as well as significantly lower rectus femoris activity ( p < 0.01) in the compliant surface condition. On the cortical level, rPDC showed significantly modulated information flow in theta and beta frequencies for fronto-parietal edges ( p < 0.01) only during the concentric phase of the movement. The compliant surface led to increased difficulties controlling hip but not center of pressure motion in the medio-lateral plane. Moreover, a decreased activation of the prime movers accompanied by modulations of effective brain connectivity among fronto-central nodes may point to altered demands on sensorimotor information processing in presence of sensory noise when performing bodyweight squats on compliant surface. Further studies are needed to evaluate a potential benefit for athletic and clinical populations.

Disturbance from tillage is a dominant factor in explaining differences in soil biodiversity of three grasslands management types - Nick van Eekeren; Jurre Dekker; Rob Geerts; Pedro Janssen; Anthonie Stip; Tim Visser; Jaap Bloem; Ron de Goede (Applied Soil Ecology, 2025)

Shifts in phytoplankton and zooplankton communities in three cyanobacteria-dominated lakes after treatment with hydrogen peroxide - Tim Piel; Giovanni Sandrini; Erik F.J. Weenink; Hongjie Qin; Maria J. van Herk; Mariël Léon Morales-Grooters; J. Merijn Schuurmans; Pieter C. Slot; Geert Wijn; Jasper Arntz; Sevasti-Kiriaki Zervou; Triantafyllos Kaloudis; et al. (Harmful Algae, 2024)

Modelling land condition to augment Land Degradation Neutrality assessments - The succulent Karoo biome of South Africa as a case study - Wesley Bell; M Timm Hoffman; Vernon Visser; Tim Kirsten (Journal of Arid Environments, 2023)

A regional, remote sensing-based approach to mapping land degradation in the Little Karoo, South Africa - Tim Kirsten; Michael Timm Hoffman; Wesley Drummond Bell; Vernon Visser (Journal of Arid Environments, 2023)

The harmful cyanobacterium Microcystis aeruginosa PCC7806 is more resistant to hydrogen peroxide at elevated CO2 - Hongjie Qin; Giovanni Sandrini; Tim Piel; Pieter C. Slot; Jef Huisman; Petra M. Visser (Harmful Algae, 2023)

Designing sustainable innovations in manufacturing: A systems engineering approach - Tim van Erp; Cecilia Haskins; Wayne Visser; Holger Kohl; Niels Gorm Maly Rytter (Sustainable Production and Consumption, 2023)

An evaluation of different approaches which use Google Street View imagery to ground truth land degradation assessments - Wesley Drummond Bell; Vernon Visser; Tim Kirsten; Michael Timm Hoffman (Environmental Monitoring and Assessment, 2022)

Transcriptomic Responses of Potato to Drought Stress - Ernest B. Aliche; Tim Gengler; Irma Hoendervangers; Marian Oortwijn; Christian W. B. Bachem; Theo Borm; Richard G. F. Visser; C. Gerard van der Linden (Potato Research, 2022)
Transcriptomic changes in plants during drought stress give insights into the mechanisms with which plants stabilise their metabolic processes in order to cope with the drought condition. In potato, understanding such drought-induced transcriptomic changes is critical because prolonged field drought interferes with tuber formation and bulking period of potato development, which eventually affects yield. We hypothesised that phenotypic drought responses of potato genotypes may be linked to differences in transcriptomic changes. Using an RNA sequencing approach, we investigated such transcriptomic changes in leaves of three cultivars (Biogold, Hansa and Lady Rosetta) under drought. We found more differentially expressed genes (DEGs) in the tolerant cultivars, Lady Rosetta and Biogold, than in the sensitive cultivar (Hansa). The differential gene expression trend reflected the phenotypic drought responses of the cultivars. For instance, we found in both Biogold and Lady Rosetta but not in Hansa, an upregulation of genes involved in carbohydrate metabolism (e.g., Alpha-glucosidase ), flavonoid biosynthesis (e.g., Flavanone 3 beta-hydroxylase ), lipid biosynthesis/transfer (e.g., nonspecific Lipid Transfer Proteins ), heat shock proteins and secondary metabolites like phenolics and lignins. Furthermore, a prolonged drought stress resulted in reduced DEGs in Biogold and Hansa, but not in Lady Rosetta that also maintained its tuber yield under such prolonged stress suggesting a more robust drought tolerance. Our findings suggest that a synergistic expression of genes involved in several different aspects of drought response is required in order to obtain a robust tolerance.

Interspecific protection against oxidative stress: green algae protect harmful cyanobacteria against hydrogen peroxide - Erik F. J. Weenink; Hans C. P. Matthijs; J. Merijn Schuurmans; Tim Piel; Maria J. van Herk; Corrien A. M. Sigon; Petra M. Visser; Jef Huisman (Environmental Microbiology, 2021)
Summary Oceanographic studies have shown that heterotrophic bacteria can protect marine cyanobacteria against oxidative stress caused by hydrogen peroxide (H 2 O 2 ). Could a similar interspecific protection play a role in freshwater ecosystems? In a series of laboratory experiments and two lake treatments, we demonstrate that freshwater cyanobacteria are sensitive to H 2 O 2 but can be protected by less‐sensitive species such as green algae. Our laboratory results show that green algae degrade H 2 O 2 much faster than cyanobacteria. Consequently, the cyanobacterium Microcystis was able to survive at higher H 2 O 2 concentrations in mixtures with the green alga Chlorella than in monoculture. Interestingly, even the lysate of destructed Chlorella was capable to protect Microcystis , indicating a two‐component H 2 O 2 degradation system in which Chlorella provided antioxidant enzymes and Microcystis the reductants. The level of interspecific protection provided to Microcystis depended on the density of Chlorella . These findings have implications for the mitigation of toxic cyanobacterial blooms, which threaten the water quality of many eutrophic lakes and reservoirs worldwide. In several lakes, H 2 O 2 has been successfully applied to suppress cyanobacterial blooms. Our results demonstrate that high densities of green algae can interfere with these lake treatments, as they may rapidly degrade the added H 2 O 2 and thereby protect the bloom‐forming cyanobacteria.

Impact of Different Lignin Fractions on Saccharification Efficiency in Diverse Species of the Bioenergy Crop Miscanthus - Tim van der Weijde; Andres F. Torres; Oene Dolstra; Annemarie Dechesne; Richard G. F. Visser; Luisa M. Trindade (BioEnergy Research, 2016)

Cell Wall Diversity in Forage Maize: Genetic Complexity and Bioenergy Potential - Andres F. Torres; Cornelie M. M. Noordam-Boot; Oene Dolstra; Tim van der Weijde; Eliette Combes; Philippe Dufour; Louis Vlaswinkel; Richard G. F. Visser; Luisa M. Trindade (BioEnergy Research, 2015)

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

Effect of Maize Biomass Composition on the Optimization of Dilute-Acid Pretreatments and Enzymatic Saccharification - Andres F. Torres; Tim van der Weijde; Oene Dolstra; Richard G. F. Visser; Luisa M. Trindade (BioEnergy Research, 2013)